PERAN KOPERASI DALAM PEMBERDAYAAN EKONOMI BERBASIS MASYARAKAT DI KOTA PAREPARE - Sumardi Sumardi; Muhammad Hatta; Fitriyani Syukri; Hernianti Harun (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2026)
This study examines the role of cooperatives in community-based economic empowerment in Parepare City, South Sulawesi, Indonesia. Cooperatives are constitutionally recognized under Article 33 of the 1945 Indonesian Constitution as the primary pillar of a people-based economy (ekonomi kerakyatan). Despite this mandate, cooperatives in Parepare City have faced significant decline due to limited capital access, weak human resource capacity, and intensifying competition from private enterprises and digital financial platforms. This study employs a qualitative descriptive approach. Data were collected through in-depth interviews with six purposively selected informants, supplemented by participatory observation and document analysis. Data validity was ensured through source triangulation and member-checking procedures. Findings show that cooperatives in Parepare City have performed their empowerment functions through financial services, goods distribution, and MSME support. However, four structural constraints were identified: insufficient capital accumulation, weak governance capacity, low digital technology adoption, and limited public awareness. The study recommends systemic interventions in capacity building, institutional governance reform, and digital transformation to optimize cooperative roles as agents of community economic empowerment.